THE ENERGY-EFFICIENT CHAMBER DRYER FOR DRYING MEAT PRODUCTS - Zh. Petrova; V. Paziuk; K. Samoilenko; V. Vyshnevskyi; P. Petrov; I. Koval (Harčova Nauka ì Tehnologìâ)
Chicken meat is in critical demand as it is a staple in many diets around the world. This is crucial to meeting the demand for high-quality meat on a global scale. Chicken breast is a popular and widely used source of protein. Therefore, preserving fresh meat plays an important role in combating global food shortages. One type of meat preservation is the drying process, which has a centuries-old history in many cultures around the world. Since it is not necessary to use monosodium glutamate, sodium nitrite, food colorings, flavorings, anti-caking agents, etc. Today, there are known methods of drying meat in chamber, duct, cabinet dryers, as well as in the open air. Considering the duration of these drying methods, the raw materials are specially treated before drying. The main disadvantages of the convective method of drying meat in chamber, channel, and cabinet dryers are the loss of soluble proteins in the dry product and the significant duration of the process, therefore, improving existing technologies is an urgent task. The requirements for modern food products are to preserve the biologically active substances of meat raw materials after drying and to reduce energy consumption for the process. Another important criterion for the quality of dried meat is its ability to absorb water during use. This article presents the results of experimental studies of the kinetics of drying chicken meat in a developed energy-efficient chamber dryer using a change in the direction of the heat flow. The process can be intensified by either preliminary preparation of the raw materials for drying or by increasing the heat carrier temperature. This paper highlights an experimental study where the main parameter, for the purpose of intensification, is the change in the direction of the coolant flow during the process. This reduced the process time by 20%. When analyzing the drying process, it was proven that due to the applied change in the direction of the heat flow for 120 min, more intensive evaporation of moisture from the tested sample occurs and the drying duration is reduced. Energy consumption and efficiency of the drying process were calculated depending on the change in flow direction.